Tinjauan Literatur Sistematis Perbandingan Metode Optimasi Dan Peningkatan Produksi Pada Industri Minyak dan Gas Bumi - Jefri Ripang (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This systematic literature review compares oil and gas production optimization methods using artificial lift systems, namely the Electrical Submersible Pump (ESP) and Sucker Rod Pump (SRP), as well as tertiary production enhancement methods, including Enhanced Oil Recovery (EOR) and Microbial Enhanced Oil Recovery (MEOR). Through a Systematic Literature Review (SLR) of five selected journal articles published between 2020 and 2024, this study identifies optimization strategies such as pump redesign based on the Inflow Performance Relationship (IPR) curve, optimization of pump operating parameters, selection of appropriate EOR methods according to reservoir characteristics, and the utilization of microorganisms as an alternative approach to enhance oil recovery. The findings indicate that artificial lift optimization can significantly and quantitatively improve production rates, with production increasing by up to 18 times in the ESP case study of Well X, the volumetric efficiency of the SRP increasing from 62.92% to 74% in Well A-21, and the selection of a more efficient pump type for Well MFR-21. In contrast, EOR and MEOR are more conceptual approaches applicable to the tertiary recovery stage, with their effectiveness being highly dependent on the specific reservoir characteristics of each field.